On enveloping C^*-algebra of one affine Temperley-Lieb algebra - Savchuk, Yu. (Methods of Functional Analysis and Topology, 2006)
C^*-algebras generated by orthogonal projections satisfying relations of Temperley-Lieb type are constructed.